2020
DOI: 10.1177/0886260520909195
|View full text |Cite
|
Sign up to set email alerts
|

“It Will Ruin His Career”: Does Violence Against Women Really Damage the Careers of NBA Players?

Abstract: Arrests for acts of violence against women are a common occurrence for professional athletes, including National Basketball Association (NBA) players. Many sports fans, players, and those involved in professional sport believe that arrests for acts of violence against women, whether they result in a conviction or not, are highly detrimental to an athlete’s career. We matched all 30 NBA players arrested for acts of violence against women between 2000 and 2016 with similar players who were not arrested and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Though it is not clear whether athletes commit more acts of violence than those in the general population (Kreager, 2007), male athlete violence, and specifically male sexual and domestic violence against women (hereafter ‘VAW’) frequently makes headlines in sports news (Anderson, 2017). While studies have shown that, contrary to popular belief, the careers of athletes arrested for an act of VAW are not systematically negatively impacted by arrests (Sailofsky, 2023; Sailofsky and Shor, 2022), some accused athletes are released from their employment with an organization, as the team purports to ‘take a stand’ against their violent behaviour. While an optimistic reading of these team decisions might suggest that sport organizations assess the facts of the case and make employment decisions based on whether the player actually engaged in the alleged violent behaviour, a cursory glance at arrested athletes’ careers following arrests reveal that the veracity of the allegation and the harm caused by the alleged behaviour are far from the only factors considered.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Though it is not clear whether athletes commit more acts of violence than those in the general population (Kreager, 2007), male athlete violence, and specifically male sexual and domestic violence against women (hereafter ‘VAW’) frequently makes headlines in sports news (Anderson, 2017). While studies have shown that, contrary to popular belief, the careers of athletes arrested for an act of VAW are not systematically negatively impacted by arrests (Sailofsky, 2023; Sailofsky and Shor, 2022), some accused athletes are released from their employment with an organization, as the team purports to ‘take a stand’ against their violent behaviour. While an optimistic reading of these team decisions might suggest that sport organizations assess the facts of the case and make employment decisions based on whether the player actually engaged in the alleged violent behaviour, a cursory glance at arrested athletes’ careers following arrests reveal that the veracity of the allegation and the harm caused by the alleged behaviour are far from the only factors considered.…”
Section: Introductionmentioning
confidence: 83%
“…While team decision makers all noted that VAW was unacceptable, and nearly all of them mentioned this type of physical violence when asked about more severe crimes, the actions taken by teams regarding accused players mostly tell a different story (Sailofsky, 2023; Sailofsky and Shor, 2022). If organizations had a zero-tolerance, morality-based policy to criminality or to VAW, the talent and productivity of a player would not have any impact on a player’s evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that athletes in general (Leal et al, 2015;Young et al, 2017) and football players specifically (Gage, 2008;Leal et al, 2015) commit and are arrested for more acts of VAW than men in the general population, though these findings are not unanimous (McCray, 2015;Schwartz, 2021). While research suggests that sanctions for athlete acts of VAW are negligible (Sailofsky & Shor, 2022;Withers, 2010), many sports fans still believe that arrests and criminal allegations are likely to ruin an athlete's career (Delgado, 2014;TMZ, 2018).…”
Section: Introductionmentioning
confidence: 99%